Efficient elimination of airborne pathogens: a study on aerosolized Mycobacterium tuberculosis and SARS-CoV-2 using ZeBox technology. (November 2022) - Narayan, R.; Kundu, D.; Ghatak, A.; Tripathi, S.; Datta, S.
Summary: Background: Despite multifactorial evidence, the safe and effective elimination of free-floating micro-organisms remains a significant scientific challenge. ZeBox Technology exploits microbial Zeta Potential, to extract and eliminate them from free-flowing air, using a non-ionizing electric field, in combination with a microbicidal surface. Aim: Evaluation of ZeBox Technology against aerosolized SARS-CoV-2 and Mycobacterium tuberculosis under controlled conditions. Methods: SARS-CoV-2 and M. tuberculosis H37Ra were used in this study. Individual micro-organisms were aerosolized using a Collison nebulizer inside an air-sealed test chamber. Air samples were collected from the chamber on to a Mixed Cellulose Ester membrane, at various time points, and used for enumeration. SARS-CoV-2 was enumerated using qRT-PCR, while M. tuberculosis H37Ra was quantified using standard microbiological procedures. Findings: We established a viable aerosolized microbial load of ∼10E9 and ∼10E6 for SARS-CoV-2 and M. tuberculosis H37Ra, respectively, inside the test chamber. Under ideal conditions, the floating microbial load was at a steady-state level of 10E9 for SARS-CoV-2 and 10E6 for M. tuberculosis . When the ZeBox-Technology-enabled device was operated, the microbial load reduced significantly. A reduction of ∼10E4.7 was observed for M. tuberculosis, while a reduction of ∼10E7 for SARS-CoV-2 was observed within a short duration. The reduction in airborne SARS-CoV-2 load was qualitatively and quantitatively measured using fluorescence analysis and qRT-PCR methods, respectively. Conclusion: This validation demonstrates the efficacy of the developed technology against two of the deadliest micro-organisms that claim millions of lives worldwide. In conjunction with the existing reports, the present validation proved the true broad-spectrum elimination capability of ZeBox technology.